Cardiac Tamponade Secondary to Hemangiosarcoma in a Dog - Smiderle, Ana Paula; Endo, Vanessa Tiemi; Almagro, Larissa Donat; Montagni, Karim Cristhine Pase; Panini, Bruna Maíra; Paula, Carla Gomes; Viott, Aline de Marco; Jojima, Flavio Shigueru (Acta Scientiae Veterinariae, 2021)
Background: Nonspecific clinical manifestations such as apathy, anorexia and diarrhea are common in the clinical routine, and therefore may mask the severity of its triggering factor. When patients presenting this symptomatology are referred to the care center, it is essential that a thorough investigation is performed to clarify the primary causes of these manifestations, and for this, complementary imaging exams may be necessary. The objective of this study is to describe the clinical and imaging aspects of a canine with cardiac hemangiosarcoma and to correlate with the pathophysiology of the alterations observed, in order to optimize the clinical care of patients with nonspecific clinical signs and affected by this alteration. Case: A 10-year-old Pitbull dog was treated with a history of vomiting, loss of appetite and diarrhea. Upon clinical examination, the animal presented dehydration level and distended abdomen. On ultrasound examination, hepatomegaly was observed, associated with signs of double layer in the gallbladder wall and the presence of moderate peritoneal effusion. On chest radiography, the cardiac silhouette showed an important increase in size with loss of shape and contours. Dorsal displacement of the trachea, greater contact of the heart with the sternum and displacement of the caudal vena cava were observed. In addition, an amorphous and poorly defined structure with radiopacity of soft tissues was observed in the region of the atrium and right ventricle, causing the obliteration of pulmonary fields. On echocardiographic examination, a significant amount of free anechogenic fluid was observed in the pericardial sac, confirming the suspicion of pericardial effusion, with consequent collapse of the wall of the right heart chambers during systole. Furthermore, an amorphous, poorly defined and heterogeneous structure was observed in the right atrium wall. Due to the location of the neoformation, the patient’s general clinical condition, euthanasia was chosen. During the necropsy, the ocular, oral and preputial mucosae were moderately pale. In the abdomen, the presence of hydroperitoneum and hepatomegaly was observed. In the thoracic cavity, hemothorax, enlarged heart were identified and, in the right atrium, a reddish mass was identified. In addition, the lungs were whitish and hypercrepitating at the edges of the cranial lobes; the rest of the organ was moderately hyperemic, hypocrepitating. In histopathological examination of the liver, the centrilobular region showed chronic passive congestion associated with necrosis and multifocal degeneration of hepatocytes. Neoplastic proliferation of mesenchymal cells, moderately cellular, non-encapsulated, of infiltrative growth was observed in the heart. Neoplastic cells formed bundles, with a tendency to organize themselves into small blood vessels filled with red blood cells. The cytoplasm was moderate, elongated, indistinct, eosinophilic and homogeneous. The nucleus was large, unique, elongated, with finely dotted chromatin and sometimes with one or two nucleoli evident. Anisocytosis, anisocariosis and cell pleomorphism were moderate. Interwoven with neoplastic cells, a moderate presence of multifocal lymphohistioplasmocytic inflammatory infiltrate was observed. The definitive diagnosis of cardiac changes was hemangiosarcoma. Discussion: Hemangiosarcoma is a vascular endothelial cell neoplasm with high metastatic power and unfavorable prognosis. When located in the heart, it is commonly found in the auricle and right atrium and the cardiovascular changes caused by this neoplasm as well as the severity of these changes vary according to size and location. Clinical manifestations can be quite nonspecific and are usually associated with hemodynamic impairment, causing signs of right or left congestive heart failure. Keywords: heart, neoplasm, pathophysiology. Descritores: coração, neoplasia, patofisiologia. Título: Tamponamento cardíaco secundário ao hemangiossarcoma em cães